Chronobiological patterns of acute aortic dissection in central China - Xia, Liangtao (Heart, 2021)
BACKGROUND: Acute aortic dissection (AAD) is a life-threatening emergency with poor clinical outcomes. Understanding the chronological patterns of AAD onset would be helpful for identifying the triggers of AAD and preventing this catastrophic event. METHODS: We collected data from 2048 patients diagnosed with AAD at Tongji Hospital (Wuhan, China) from 2011 to 2018. The χ(2) test was used to determine whether a specific period had significantly different seasonal/weekly distributions from other periods. Fourier models were used to analyse the rhythmicity in monthly/circadian distribution. RESULTS: The mean age was 53.4±10.9 years, and 1161 patients (56.7%) were under 55 years. One thousand six hundred fifty-seven patients (80.9%) were male, and 935 cases (45.7%) were type A dissections. The proportions of patients with comorbid hypertension/diabetes were 60.3% (1234 cases) and 1.8% (36 cases), respectively. A peak was identified in colder periods (winter/December) and a trough in warmer periods (summer/June). No significant variation was observed in weekly distribution. Fourier analysis showed a statistically significant circadian variation (p<0.001) with a nocturnal trough in 2:00–3:00, a morning peak in 9:00–10:00, and an afternoon peak in 16:00–17:00. Subgroup analyses identified circadian rhythmicity in all subgroups except for the female group and younger group (younger than 55 years). CONCLUSION: Our results confirmed that the onset of AAD exhibits significant seasonal, monthly and circadian patterns. Patients with AAD with different Stanford-type dissections, sexes, ages and hypertension statuses could present different circadian variations. These findings may provide novel perspectives for identifying the triggers of AAD and better preventing this catastrophic event.